2020
DOI: 10.1142/s0219877020500406
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Product Innovation Through Digital Transformation and Absorptive Capacity

Abstract: This paper analyzes the mediating effect of absorptive capacity (AC) on the relationship between digital transformation from e-business capabilities (EBC) perspective and product innovation (PI). Structural equation modeling (SEM) was carried out with the survey data from a sample of firms that belong mainly to highly digitalized sectors. The results indicate the existence of a full mediation, which means knowledge derived from the digital operation of the business can only result in PI if AC plays an intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
0
0
3
Order By: Relevance
“…Se destaca cómo la robótica con IA está siendo implementada en la industria manufacturera para aumentar la eficiencia y la productividad en las líneas de producción. Además, se destaca cómo grandes empresas como Tesla y Amazon están utilizando robots con capacidades de IA en sus instalaciones para mejorar la velocidad y la precisión de la fabricación y la logística (Coronado, Arias, & Perdomo, 2023). Estos resultados ponen de relieve el papel crucial que juega la IA en la transformación de los procesos industriales y en la mejora de la competitividad empresarial.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Se destaca cómo la robótica con IA está siendo implementada en la industria manufacturera para aumentar la eficiencia y la productividad en las líneas de producción. Además, se destaca cómo grandes empresas como Tesla y Amazon están utilizando robots con capacidades de IA en sus instalaciones para mejorar la velocidad y la precisión de la fabricación y la logística (Coronado, Arias, & Perdomo, 2023). Estos resultados ponen de relieve el papel crucial que juega la IA en la transformación de los procesos industriales y en la mejora de la competitividad empresarial.…”
Section: Resultados Y Discusiónunclassified
“…Cabe señalar que, la innovación empresarial es un proceso multifacético que abarca la generación de nuevas ideas, la implementación de soluciones creativas y la creación de valor para los clientes y las partes interesadas (Coronado, Arias, & Perdomo, 2023). En este sentido, la inteligencia artificial puede actuar como un catalizador poderoso al automatizar tareas repetitivas, mejorar la eficiencia operativa y liberar recursos humanos para actividades más estratégicas y creativas.…”
Section: Introductionunclassified
“…Gao et al (2022), highlighted the importance of absorptive capacity in linking knowledge search with product and process innovation, underscoring that an organization's effective absorption of new knowledge contributes to its ability to generate product innovation. Furthermore, Coronado-Medina et al (2020) demonstrated that absorptive capacity mediates the relationship between digital transformation and product innovation. The organization's ability to manage and leverage new knowledge acquired from digital transformation is instrumental in achieving successful product innovation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Human capital, which encompasses the knowledge, skills, and experience of employees, has long been recognized as a valuable resource for fostering innovation (Atiase & Dzansi, 2020;Fu, Liu, Yang, Jiao, & Jin, 2020;Marvel, Wolfe, & Kuratko, 2020;You, Zhou, & Jia, 2021). However, in dynamic environments, it becomes imperative to explore absorptive capacity, contribute to innovation and potentially influence the relationship between human capital and product innovation (Akram, Ghosh, & Joseph, 2021;Coronado-Medina, Arias-Pérez, & Perdomo-Charry, 2020;Gallegos, Salvador Durand, & Soria Gomez, 2020;Gao, Ding, & Wu, 2022;Jeong, Chung, & Roh, 2019). Hence, the primary objective of this study is to examine how absorptive capacity affects the relationship between human capital and product innovation as a mediating and moderating component.…”
Section: Introductionmentioning
confidence: 99%
“…La capacidad de absorción permite a las empresas mejorar su capacidad de innovación con respecto a sus productos (Coronado-Medina et al, 2020). Murovec y Prodan (2008) analizaron la fuerte relación entre la capacidad de absorción de las empresas eslovenas y su capacidad para desarrollar innovaciones de productos.…”
Section: Capacidad De Absorción E Innovación De Productosunclassified